The primate reticulospinal tract, hand function and functional recovery - Baker, Stuart N (Blackwell Science Inc, 2011)
ABSTRACT: The primate reticulospinal tract is usually considered to control proximal and axial muscles, and to be involved mainly in gross movements such as locomotion, reaching and posture. This contrasts with the corticospinal tract, which is thought to be involved in fine control, particularly of independent finger movements. Recent data provide evidence that the reticulospinal tract can exert some influence over hand movements. Although clearly secondary to the corticospinal tract in healthy function, this could assume considerable importance after corticospinal lesion (such as following stroke), when reticulospinal systems could provide a substrate for some recovery of function. We need to understand more about the abilities of the reticular formation to process sensory input and guide motor output, so that rehabilitation strategies can be optimised to work with the innate capabilities of reticular motor control.